Perancangan Interior Sekolah Dasar dengan Penerapan Konsep Green Building - Shearen Hariono (Intra, 2017)
Humans and their living environment have a phenomenon that is mutualizes each other. The environment influences the human live and in turn humans give influence on the quality of the environment. However, in reality, the current human lifestyle tends to ignore or even damages the environment. Therefore, there needs to be a lifestyle correction that the whole community, from children to adults, should do. In this case, primary school has an important role to raise awareness of the environment in children (6-12 years old) so the importance of environment becomes one of their concerns when they do or create something. Hence, this interior design of primary school aims to provide a place where good study activities can be facilitated, i.e. from general studies to studies about the care of the environment by implementing the concept of green building. There are also green activities as a direct activity provided to educate about the environment. Green activity in this design will be in the form of school garden. Based on the calculation of green building implication criteria, this primary school design received gold with 74 points and a percentage of 71.8% with the greenship interior space version 1.0 parameter.